INCREASING THE COMPETENCE OF ISLAMIC RELIGIOUS EDUCATION TEACHERS FROM A MADRASAH-BASED MANAGEMENT PERSPECTIVE - Husnol Khotimah; Manshur, Umar; Zaini, Abdul Wahid; Sanjani, M Aqil Fahmi; Suhermanto, Suhermanto (Universitas Nurul Jadid, 2024)
This study aims to analyze and examine the model of improving the competence of Islamic religious education teachers in the perspective of Madrasah-based management, a new direction based on psychological functions towards the development and progress of teachers as educators. This study was conducted in Islamic educational institutions at the elementary madrasah level. The researcher used a qualitative case study type approach. Data were collected using interview, observation and documentation techniques and then analyzed through several steps, namely: data collection, data reduction, data presentation and conclusions. The results of the study indicate that, in an effort to improve the competence of Islamic religious education teachers in elementary madrasahs, including innovative strategies in developing teacher competencies, collaboration-based competency approach, technology integration in transforming islamic religious education learning. The results of the study are expected to provide benefits to realize the improvement of the competence of Islamic religious education teachers in elementary madrasahs from the perspective of madrasah-based management.